2022
DOI: 10.1021/jacs.1c10885
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Nuclear Quantum Effects for Molecular Cocrystals with Short Hydrogen Bonds

Abstract: Many efforts have been recently devoted to the design and investigation of multicomponent pharmaceutical solids, such as salts and cocrystals. The experimental distinction between these solid forms is often challenging. Here, we show that the transformation of a salt into a cocrystal with a short hydrogen bond does not occur as a sharp phase transition but rather a smooth shift of the positional probability of the hydrogen atoms. A combination of solid-state NMR spectroscopy, X-ray diffraction, and diffuse ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(61 citation statements)
references
References 61 publications
(58 reference statements)
1
59
1
Order By: Relevance
“…The amine protons get deshielded by 0.145 ppm whereas the aromatic protons get deshielded by 0.0949 and 0.1238 ppm respectively which is expected due to the generation of charge separated state from the cocrystal state. [ 32 ] The Raman spectra of the cocrystal 1’ shows clearly distinguishable peaks whereas the Raman spectra for the charge separated state 1 shows a broad band due to the delocalization of charge and generation of band structure in CT complex (Figures S10 and S11, Supporting Information). The solid‐state UV–vis spectra in the supporting information (Figure S12, Supporting Information) also shows the generation of a band structure in charge separated state 1 with the appearance of a broadband from 350 to 650 nm as compared to the cocrystal state 1’ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amine protons get deshielded by 0.145 ppm whereas the aromatic protons get deshielded by 0.0949 and 0.1238 ppm respectively which is expected due to the generation of charge separated state from the cocrystal state. [ 32 ] The Raman spectra of the cocrystal 1’ shows clearly distinguishable peaks whereas the Raman spectra for the charge separated state 1 shows a broad band due to the delocalization of charge and generation of band structure in CT complex (Figures S10 and S11, Supporting Information). The solid‐state UV–vis spectra in the supporting information (Figure S12, Supporting Information) also shows the generation of a band structure in charge separated state 1 with the appearance of a broadband from 350 to 650 nm as compared to the cocrystal state 1’ .…”
Section: Resultsmentioning
confidence: 99%
“…Salt to cocrystal transition for a particular multicomponent system is rare and has been recently observed through different techniques. [32][33][34][35][36][37][38][39][40] Herein we report an orthophenylene diamine (D) and pyromellitic acid (A) based novel CT complex 1 where the conduction path is established solely via H-bonding interaction. Formation of the CT complex 1 is achieved in two steps.…”
Section: Introductionmentioning
confidence: 99%
“…The hot stage microscope images (Figure S20c) and cyclic DSC curve (Figure S20d) demonstrates that there is an endothermic peak at 101.65 °C during the heating process and an exothermic peak at 98.63 °C during the cooling back to room temperature, which further demonstrates that there is a polymorph transformation during the heating and cooling processes. The temperature-variable single crystal structure analysis revealed that the PPA-GA cocrystal is the most stable form at high temperature, whereas the salt form is the most stable form at low temperature …”
Section: Resultsmentioning
confidence: 99%
“…The temperature-variable single crystal structure analysis revealed that the PPA-GA cocrystal is the most stable form at high temperature, whereas the salt form is the most stable form at low temperature. 50 3.7. Solubility Studies.…”
Section: Conformation and Packing Similarity Analysismentioning
confidence: 99%
“…It is evident from Figure 7 that the GIPAW calculated 1 H chemical shifts for the high-ppm NH2 resonances, namely 30a I , 30b I , and 30a II at 8.8, 9.5 and 10.3 ppm are significantly higher than the experimental value of 7.0 ppm. Such a discrepancy is well established for hydrogen-bonded 1 H resonances and can be explained by the known experimental temperature-dependence of such hydrogen-bonded 1 H chemical shifts [99][100][101][102][103][104][105][106][107] , whereas GIPAW calculation is effectively performed at 0 K. 108 In other words, if variable-temperature 1 H MAS NMR spectra were recorded, these 1 H resonances would move to higher ppm as the temperature is lowered.…”
Section: Heteronuclearmentioning
confidence: 99%